Rare earth nanoparticle loaded biological silicon dioxide negative electrode material and preparation and application thereof
By adding a rare earth ion solution to the diatom medium, the rare earth nanoparticles are assembled on the diatom shell with the use of diatomic biochemization to solve the problem of insufficient conductivity and cycle stability of the existing lithium -ion batteries. The lithium -ion battery negative material of high energy density and long cyclic life is achieved.
Patent Information
- Application Number
- CN202411590491.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The theoretical specific capacity of graphite anode materials of existing lithium-ion batteries is lower, and the silicon dioxide anode materials have not been able to achieve large-scale commercial application due to low conductivity and volume expansion problems. At the same time, the in vitro modification method of diatom-based biosilicon dioxide is inefficient and has a great impact on the strength of conductivity, and lacks simple and efficient in vivo modification technology.
By adding rare earth ion solutions in LACL3 and YCL3 to the diatom medium, the diatomic biomedicization effect is used to absorb and process the rare earth nanoparticles, combined with the growth process of diatoms, and prepare rare earth nano Biosilicon negative material with particle load. This method is burned in an inert atmosphere to form an ideal LA/Y/C@SiO2 material.
The biological self -assembly of rare earth nanoparticles on the diatom shell has improved the conductivity and cycle stability of the lithium -ion battery negative electrode material, and significantly increased the energy density and long cycle life of the battery.
Smart Images

Figure CN119381435A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of rare earth application and lithium ion battery negative electrode materials, and specifically relates to a rare earth nanoparticle-loaded bio-silicon dioxide negative electrode material and a preparation method and application thereof. Background Art
[0002] Traditional graphite negative electrode materials for lithium-ion batteries have a low theoretical specific capacity and are difficult to meet the needs of the current energy market. Therefore, it is urgent to develop new and more efficient alternative negative electrode materials. Therefore, many alternative negative electrode materials have emerged, such as alloy compounds, silicon, silicon dioxide, transition metal oxides, etc. Among the many alternative negative electrode materials, silicon dioxide has become a very potential negative electrode material for lithium-ion batteries due to its high theoretical specific capacity and abundance, and its extremely rich reserves on the earth. However, due to its low conductivity and certain volume expansion, it has not yet been able to achieve large-scale commercial applications. Among the many sources of silicon dioxide, diatoms are a natural, green and abundant source of silicon dioxide.
[0003] Since diatoms were reported to be a source of active negative electrode materials for lithium-ion batteries, they have attracted great attention. Because diatoms have a hollow and porous silica shell structure, compared with general silica sources, diatom biosilica significantly alleviates the volume expansion of silica during the cycle, and has a significant effect on the performance improvement of silica negative electrode materials. Therefore, most studies focus on the in vitro modification of diatom-based biosilica to improve the conductivity of silica. Common modification methods include combining diatom-based biosilica with conductive carbon precursors or metal ions to improve the intrinsic conductivity of silica negative electrode materials. However, most in vitro modification methods have problems such as low efficiency and easy detachment of the loaded conductive phase. The conductivity of the loaded metal itself will also have a great impact on the performance of the electrode material. Research on the in vivo modification of diatoms to achieve the performance improvement of diatom-based biosilica negative electrode materials is still relatively lacking. Therefore, seeking a simpler and more efficient technology for in vivo modification of diatoms to improve the conductivity of silica is an urgent need in this field.
[0004] Research on rare earth elements in the field of energy storage has attracted great attention, especially in the field of lithium-ion batteries. It is worth noting that most of the research focuses on improving the properties of rare earth element-doped cathode materials. For example, Zhang et al. (https: / / doi.org / 10.1007 / s10853-023-08542-z) prepared La and Y-doped LiFePO4 cathode materials by a one-step hydrothermal method, proving that La and Y can expand the lattice fringes of LiFePO4, improve the ion diffusion efficiency and the electronic conductivity of the material, and have a positive effect on the electrochemical performance of the cathode material. However, the disadvantage of this method is that the preparation method of the material is complicated and the content of the doped rare earth elements is difficult to control, and it is not possible to observe the obvious distribution of rare earth elements on the composite material.
[0005] After searching the literature of the prior art, it was found that Chinese patent CN202311770215.7 discloses a modified diatom material and its preparation method and application. By preparing an ionic rare earth ore extract or wrapping the ionic rare earth ore with a semipermeable membrane to co-cultivate diatoms, a rare earth co-cultivated modified diatom material was obtained. The prepared lithium-ion battery has a capacity of about 820 mAh·g after 35 cycles. -1 The invention has the following disadvantages: the composition of the ionic rare earth ore used is unclear, the rare earth loading is low, and no obvious rare earth nanoparticles are observed on the diatom shell, indicating that the rare earth ore or rare earth ore extract cannot be well utilized during the growth of diatoms. Summary of the invention
[0006] The purpose of the present invention is to combine the research and exploration of the prior art to provide a rare earth nanoparticle-loaded bio-silica material and its preparation method and application, so as to develop a lithium-ion battery negative electrode material with high energy density and long cycle life. The specific technical scheme is as follows:
[0007] The present invention is achieved in the following ways:
[0008] A rare earth nanoparticle-loaded biological silicon dioxide negative electrode material is obtained by utilizing the biomineralization of diatoms to absorb rare earth elements into diatom cells by using at least one of LaCl3 and YCl3 as an additive to diatom growth medium and processing the rare earth elements into rare earth nanoparticles, which are then calcined in an inert atmosphere.
[0009] The method for preparing the rare earth nanoparticle-loaded bio-silicon dioxide negative electrode material comprises the following steps:
[0010] 1) Rare earth nanoparticle loading of diatoms: rare earth ion solution is added to diatom culture medium and diatoms are inoculated for co-cultivation;
[0011] 2) Diatom collection and pretreatment: After the culture cycle is over, the algae solution is filtered or centrifuged to obtain a diatom precipitate, which is then washed with at least one of hydrochloric acid or sulfuric acid. The acid-washed diatom solution is separated into solid and liquid, and the precipitate is collected and washed with at least one of methanol or ethanol. After solid-liquid separation, the diatom precipitate is collected;
[0012] 3) The diatom precipitate loaded with rare earth nanoparticles is freeze-dried and calcined at high temperature to obtain a bio-silica composite material loaded with rare earth nanoparticles.
[0013] Step 1) preparing a solution of at least one of LaCl3 and YCl3 with a concentration of 0.1 g / L-1 g / L.
[0014] Step 1) Add 5-20 mL of rare earth compound solution to 1-2 L of diatom culture medium and inoculate 100-200 mL of diatom seed solution.
[0015] Step 1) The diatom culture period is 10 days to 14 days, the culture temperature is 22°C to 25°C, the light intensity is 2000 Lux to 4000 Lux, and the diatoms are statically cultured in a light incubator.
[0016] Step 2) Collect the algae liquid after culture for acid washing; specifically, the enriched algae liquid is acid washed with 2%-5% dilute hydrochloric acid; after acid washing, the mixture is centrifuged at 8000-10000 r / min for at least 10 min, and the precipitate is collected for solid-liquid separation; the precipitate after acid washing is washed with ethanol 1-2 times until the washing liquid is colorless and transparent.
[0017] Step 3) Freeze-dry the diatom pellet at -70°C for at least 24 h.
[0018] Step 3) The dried diatom mixture is heated to 600-900°C at a rate of 5°C - 10°C / min under an argon atmosphere and kept at this temperature for 1 h - 3 h.
[0019] The preferred heating rate is 5 °C / min, the calcination temperature is 600 °C, and the holding time is 3 h.
[0020] The present invention also provides the use of the rare earth nanoparticle-loaded biosilicon dioxide in negative electrode materials for lithium-ion batteries.
[0021] Furthermore, it is used for preparing negative electrode materials for lithium-ion batteries.
[0022] The active material prepared by the present invention is mixed with Super P and PVDF in a mass ratio of 7:2:1 or 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) is added, and ball milling is performed at 300 to 450 r / min for 1 to 3 hours to obtain a uniformly mixed electrode slurry, and the slurry is coated on a copper foil with a thickness of 25 to 300 μm, vacuum dried at 80 ° C, and cut to obtain an electrode sheet. Preferably, the ratio of active material: Super P: PVDF = 7:2:1, ball milling is performed at 300 r / min for 3 hours, and the slurry coating thickness is 50 μm.
[0023] Continue to place the cut electrode sheets on the battery bottom shell in the argon-filled glove box, add 1 to 2 drops of electrolyte on the surface of the electrode sheets, place the diaphragm, add 1 to 2 drops of electrolyte, and finally put in the lithium sheet, cover the battery cover, and seal it on the button battery packaging machine to complete the battery assembly.
[0024] In the above-mentioned drying and calcination process, calcination in an argon environment converts the residual cytoplasm in the diatom cells into a carbon layer to obtain an ideal La / Y / C@SiO2 material. The above-mentioned method is fast and simple, and can be commercialized by expanding the experiment, designing a reasonable process flow, and finally realizing commercialization.
[0025] The difference between the present invention and the method disclosed in the prior art is that the present invention uses rare earth chloride as a modifier for diatom culture medium, and utilizes the biomineralization of diatoms during the growth and metabolism process to enrich La and Y into the diatom shell structure. The biological self-assembly of rare earth nanoparticles on the diatom shell is achieved, which is different from the traditional method of solid-phase self-assembly composite of ready-made diatom raw materials with other substances. It also overcomes the defect of the prior art that rare earth ores or rare earth ore extracts cannot be well utilized during the growth of diatoms. Moreover, the entire operation process is simple and easy, with high safety, low economic cost, easy access to raw materials, and friendly to the ecological environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The XRD patterns of Example 1, Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 of the present invention are shown in FIG.
[0027] Figure 2 The transmission electron microscope and scanning electron microscope images of Comparative Example 1 (a), Comparative Example 2 (b), Example 2 (c), and Example 4 (d) of the present invention are shown. In the transmission electron microscope images of Comparative Example 1 and Comparative Example 2, the surface of the diatom shell is smooth and free of load. In the transmission electron microscope images and scanning electron microscope images of Example 2 and Example 4, La and Y nanoparticles distributed on the surface of the diatom shell can be observed.
[0028] Figure 3The present invention is Example 1, Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 at 100 mA·g -1 Long cycle performance curve under current density.
[0029] Figure 4 These are cyclic voltammetry test curves of Comparative Example 1, Comparative Example 2, Example 1, Example 2, Example 3 and Example 4 of the present invention.
[0030] Figure 5 1 and 2 are rate performance curves of Comparative Example 1, Comparative Example 2, Example 1, Example 2, Example 3 and Example 4 of the present invention.
[0031] Figure 6 These are the electrochemical AC impedance test spectra of Comparative Example 1, Comparative Example 2, Example 1, Example 2, Example 3 and Example 4 of the present invention.
[0032] Figure 7 Soft X-ray nano-CT images of Example 2 of the present invention, (a) is a 3D structural diagram of the original diatom, and (b) is a three-dimensional distribution diagram of La nanoparticles in the diatom shell. DETAILED DESCRIPTION
[0033] In order to explain in detail the preparation method of the material of the present invention and its application in the negative electrode material of lithium ion batteries, further description is given below in conjunction with specific embodiments and accompanying drawings.
[0034] Example 1
[0035] (1) Prepare a 1 g / L lanthanum chloride solution, add 2 mL of 1 g / L lanthanum chloride solution to 2 L of diatom culture medium, shake well, inoculate 200 mL of diatom seed solution, and place in a light incubator for 10 days. The culture temperature is 25°C and the light intensity is 4000 Lux.
[0036] (2) Filter the cultured algae solution to obtain an enriched algae solution, add 5% hydrochloric acid to the enriched algae solution in (1), and allow the hydrochloric acid to react with the carbonate to remove impurities for 3 hours to obtain a hydrochloric acid diatom mixed solution;
[0037] (3) Centrifuge the HCl diatom mixture in (2) at 8000 rpm for 10 min, remove the supernatant, and obtain the diatom precipitate treated with hydrochloric acid;
[0038] (4) adding ethanol to the diatom precipitate after acid washing with HCl solution in (3) to extract the pigment and impurity ions in the diatom cells to obtain an ethanol mixed solution;
[0039] Dosage: Add 50 mL of ethanol to the diatom precipitate obtained in step (4).
[0040] (5) Centrifuge the ethanol mixture in (4) at 5000 rpm for 10 min, remove the supernatant, and obtain the diatom precipitate treated with ethanol;
[0041] (6) freeze-drying the diatom precipitate obtained in (5) at -70°C to obtain a modified diatom material;
[0042] (7) The modified diatom material in (6) was heated to 600°C at a rate of 5°C / min under an argon atmosphere and calcined at high temperature for 3 h to obtain a La nanoparticle-loaded bio-silica negative electrode material (DBS@C-La-1).
[0043] (8) The active material prepared in the present invention was mixed with Super P and PVDF in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added. The mixture was ball-milled at 500 r / min for 3 h to obtain a uniformly mixed electrode slurry. The slurry was coated on a copper foil with a thickness of 50 μm, vacuum dried at 80 °C, and cut to obtain an electrode sheet. After cutting, a circular electrode sheet with a diameter of 12 mm was obtained.
[0044] (9) Place the cut electrode sheet on the lower shell of the battery in an argon-filled glove box, add 1 drop of electrolyte on the surface of the electrode sheet, place the diaphragm, add another drop of electrolyte, and finally put in the lithium sheet. Cover the battery with the upper cover and seal it on a button cell packaging machine to complete the battery assembly.
[0045] (10) The assembled battery was subjected to impedance spectroscopy testing on a Gamry electrochemical workstation with a test frequency range of 100 kHz to 0.01 Hz. The impedance spectroscopy results are shown in Figure 6 As shown, the charge transfer impedance is small. The assembled battery is subjected to constant current charge and discharge test on the LAND battery charge and discharge test system, and the test voltage range is 0.001 ~ 3.0 V (vs. Li / Li + ), the current density is 100 mA g -1 , the long cycle performance curve is as follows Figure 3 As shown in Figure 2, the electrode can achieve ~782 mAh g after 150 cycles. -1 The assembled battery was subjected to cyclic voltammetry test on an electrochemical workstation with a test voltage range of 0.001 ~ 3.0 V (vs. Li / Li + ), the cyclic voltammetry curve is as follows Figure 4 As shown in c, additional redox peaks can be observed in the cyclic voltammetry curve, indicating that La participates in the redox reaction of the electrochemical system and improves the discharge capacity. Figure 5 As shown, the rate performance is good.
[0046] Embodiment 2: The difference from Embodiment 1 is only that:
[0047] Prepare a 1 g / L lanthanum chloride solution, add 20 mL of 1 g / L lanthanum chloride solution to 2 L of diatom culture medium, and follow the same steps to prepare La nanoparticle-loaded diatom biogenic silica electrode material (DBS@C-La-10).
[0048] The assembled battery was tested for impedance spectroscopy on a Gamry electrochemical workstation with a test frequency range of 100kHz to 0.01 Hz. The impedance spectroscopy results are shown in the figure below. Figure 6 As shown, the charge transfer impedance is small. The assembled battery was subjected to a cycle charge and discharge test on the LAND battery charge and discharge test system, with a test voltage range of 0.001 ~ 3.0 V (vs. Li / Li + ), the current density is 100 mA g -1 , the long cycle curve is as follows Figure 3 As shown in Figure 2, the electrode obtained ~ 843 mAh·g after 150 cycles. -1 The assembled battery was subjected to cyclic voltammetry test on an electrochemical workstation with a test voltage range of 0.001 ~ 3.0 V (vs. Li / Li + ), the cyclic voltammetry curve is as follows Figure 4 d, the rate performance is Figure 6 As shown, the magnification performance is good. Through transmission electron microscopy, obvious La nanoparticles can be observed on the surface of diatom shells. Figure 7 It can be seen that La exists not only on the surface of diatom shells, but also inside the shells, realizing the in vivo and in vitro modification of diatom shells by La nanoparticles.
[0049] Embodiment 3: The difference from Embodiment 1 is only that:
[0050] The configured rare earth element is yttrium chloride with a concentration of 1 g / L. 2 mL of yttrium chloride solution with a concentration of 1 g / L is added to 2 L of diatom culture medium. The remaining steps are the same as those in Example 1 to prepare a diatom biosilica electrode material (DBS@CY-1) loaded with Y nanoparticles.
[0051] The assembled battery was tested for impedance spectroscopy on a Gamry electrochemical workstation with a test frequency range of 100kHz to 0.01 Hz. The impedance spectroscopy results are shown in the figure below. Figure 6 As shown in the figure, the assembled battery was subjected to a cycle charge and discharge test on the LAND battery charge and discharge test system, with the test voltage range of 0.001 ~ 3.0 V (vs. Li / Li +), the current density is 100 mA g -1 , the long cycle curve is as follows Figure 3 As shown in Figure 2, the electrode obtained ~707 mAh·g after 150 cycles. -1 The assembled battery was subjected to cyclic voltammetry test on an electrochemical workstation with a test voltage range of 0.001 ~3.0 V (vs. Li / Li + ), the cyclic voltammetry curve is as follows Figure 4 e, the rate performance curve is as follows Figure 5 As shown, the rate performance is good.
[0052] Embodiment 4: The difference from Embodiment 1 is only that:
[0053] The rare earth element configured was yttrium chloride with a concentration of 1 g / L. 20 mL of 1 g / L yttrium chloride solution was added to 2 L of diatom culture medium. The rest of the steps were the same to prepare the Y nanoparticle-loaded diatom biosilica negative electrode material (DBS@CY-10).
[0054] The assembled battery was tested for impedance spectroscopy on a Gamry electrochemical workstation with a test frequency range of 100kHz to 0.01 Hz. The impedance spectroscopy results are shown in the figure below. Figure 6 As shown in the figure, the assembled battery was subjected to a cycle charge and discharge test on the LAND battery charge and discharge test system, with the test voltage range of 0.001 ~ 3.0 V (vs. Li / Li + ), the current density is 100 mA g -1 , the long cycle curve is as follows Figure 3 As shown in Figure 2, the electrode obtained ~743 mAh·g after 150 cycles. -1 The assembled battery was subjected to cyclic voltammetry test on an electrochemical workstation with a test voltage range of 0.001 ~3.0 V (vs. Li / Li + ), the cyclic voltammetry curve is as follows Figure 4 f, the rate performance curve is as follows Figure 5 As shown. Through transmission electron microscopy, obvious Y nanoparticles can be observed on the surface of diatom shells.
[0055] Comparative Example 1:
[0056] This comparative example provides an untreated diatom material, which differs from the embodiment only in that:
[0057] No rare earth compound solution was added during the culture step, and the other steps remained unchanged.
[0058] The diatom material (DBS@C) obtained in Comparative Example 1 was observed to have a relatively smooth surface and no nanoparticle loading by transmission electron microscopy and scanning electron microscopy. Its capacity was lower than that of the modified diatom materials described in Examples 1, 2, 3, and 4, and its capacity and cycle stability were poor, and its impedance was large. After 150 cycles, the discharge specific capacity was 304 mAh·g -1 , the cyclic voltammetry test curve is as follows Figure 4 As shown in a, the rate performance curve is Figure 6 As shown, the rate performance is poor.
[0059] Comparative Example 2:
[0060] This comparative example provides a modified diatom material obtained by culturing diatoms using a semipermeable membrane wrapped ionic rare earth ore. The difference from Example 1 is that lanthanum chloride or yttrium chloride is not used for culturing in the culturing step, and the ionic rare earth ore is wrapped with a semipermeable membrane and added to the diatom culture medium for culturing. The specific steps are as follows:
[0061] Weigh 2.0 g of ionic rare earth ore raw material from Jianghua, Hunan. The ionic rare earth ore contains 16 rare earth elements (lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, and yttrium) as well as silicon and aluminum. Wrap it with a semipermeable membrane with a molecular weight cutoff of 8000D and place it in 2 L culture medium for co-cultivation with diatoms. The initial total rare earth ion content of the culture system is about 10.4 mg.
[0062] The remaining steps remain unchanged. The obtained semipermeable membrane wrapped cultured diatom composite material is named DBS@C-REE-2.0. Scanning electron microscopy and transmission electron microscopy showed that the diatom surface was relatively smooth and had no rare earth nanoparticle loading. The cyclic voltammetry test curve is as follows: Figure 4 As shown in b, the rate performance is poor. Compared with the modified diatom materials described in Examples 1, 2, 3, and 4, the electrode material in Comparative Example 2 has poor capacity and cycle stability, and a large charge transfer impedance. After 150 cycles, the discharge capacity is 380 mAh·g -1 , the rare earth nanoparticle-loaded diatom biosilica material exhibited excellent electrochemical performance in the battery test procedure, illustrating the effectiveness of the present modification method.
Claims
1. A rare earth nanoparticle-loaded bio-silica negative electrode material, characterized in that: The biomineralization of diatoms is utilized to take at least one of LaCl3 and YCl3 as an additive to the diatom growth medium, so that the rare earth elements are absorbed into the diatom cells and processed into rare earth nanoparticles, which are then calcined in an inert atmosphere.
2. The method for preparing the rare earth nanoparticle-loaded bio-silica negative electrode material according to claim 1 comprises the following steps: 1) Rare earth nanoparticle loading of diatoms: rare earth ion solution is added to diatom culture medium and diatoms are inoculated for cultivation; 2) Diatom collection and pretreatment: After the culture cycle is over, the algae solution is filtered or centrifuged to obtain a diatom precipitate, which is then washed with at least one of hydrochloric acid or sulfuric acid. The acid-washed diatom solution is separated into solid and liquid, and the precipitate is collected and washed with at least one of methanol or ethanol. After solid-liquid separation, the diatom precipitate is collected; 3) The diatom precipitate loaded with rare earth nanoparticles is freeze-dried and calcined at high temperature to obtain a bio-silica composite material loaded with rare earth nanoparticles.
3. The method according to claim 2, characterized in that: Step 1) preparing a solution of at least one of LaCl3 and YCl3 with a concentration of 0.1 g / L-1 g / L.
4. The method according to claim 2 or 3, characterized in that: Step 1) Add 5-20 mL of rare earth compound solution to 1-2 L of diatom culture medium and inoculate 100-200 mL of diatom seed solution.
5. The method according to claim 2, 3 or 4, characterized in that: Step 1) The diatom culture period is 10-14 days, the culture temperature is 22℃-25℃, and the light intensity is 2000 Lx - 4000 Lx.
6. The method according to claim 2 or 3, characterized in that: Step 2) Collect the algae liquid after culture for acid washing; specifically, the enriched algae liquid is acid washed with 2%-5% dilute hydrochloric acid; after acid washing, the mixture is centrifuged at 8000-10000 r / min for at least 10 min, and the precipitate is collected for solid-liquid separation; the precipitate after acid washing is washed with ethanol 1-2 times until the washing liquid is colorless and transparent.
7. The method according to claim 2 or 3, characterized in that: Step 3) Freeze-dry the diatom pellet at -70°C for at least 24 h.
8. The method according to claim 3 or 4, characterized in that Step 3) The dried diatom mixture is heated to 600-900°C at a rate of 5°C - 10°C / min under an argon atmosphere and kept at this temperature for 1 h - 3 h.
9. The use of the rare earth nanoparticle-loaded bio-silica negative electrode material obtained by the method described in claim 1 or any one of claims 2 to 8, characterized in that: Used for the preparation of negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Filler particle for adsorbing inorganic phosphorus in wastewater
CN112337440A
Modified diatom material as well as preparation method and application thereof
CN117720111A
Process for preparing rare-earth enveloping light transmission material
CN1648172A
Rare earth auxiliary agent and preparation method therefor
WO2023051150A1